Implementasi Program Rawat Inap Korban Penyalahgunaan Narkoba di Provinsi Kalimantan Barat - Sari, Ade Risna (Journal of Research and Development on Public Policy, 2023)
Rehabilitation is one of the government's efforts to deal with addicts and victims of narcotics abuse. This has been regulated in Law No. 35 of 2009 concerning Narcotics. The West Kalimantan Provincial National Narcotics Agency (BNNP) is the leading sector in handling drugs in West Kalimantan which has a program and also runs inpatient and outpatient rehabilitation programs for victims of drug abuse. In implementing the inpatient program there are obstacles. These obstacles include the lack of human resources (HR) and the lack of infrastructure or free inpatient care. The aim of this research is to find out how the inpatient rehabilitation program for drug abuse victims is implemented in West Kalimantan province, as well as to describe the factors that influence the implementation of the inpatient rehabilitation program for drug abuse victims in West Kalimantan province. The main assumption of this research is that there are several factors that influence the implementation of the inpatient rehabilitation program for drug abuse victims in West Kalimantan province, referring to George C. Edward III's theory, namely 1) communication factors; 2) resource factors; 3) disposition factors; and organizational structure factors. This research was analyzed using qualitative methods with a descriptive approach. The research results were obtained by observing and interviewing all key informants and supporting informants as well as using documentation techniques and literature study.